Indices of skewness derived from a set of symmetric quantiles - Brizzi, Maurizio (Metodološki zvezki, 2007)
In this paper, which follows a recent field of research started by Tukey (1977), a class of indices of skewness is introduced, based on a symmetric set of quantiles. Two kinds of normaisation are proposed, leading to different indices, called VCS (Ventile Coefficient of Skewness) and VIS (Ventile Index of Slewness), respectively. The sample distribution of both indices is studied by a Monte Carlo simulation. Two extended indices of skewness (ECS and EIS) are proposed, having interesting inferential properties. Finally, an application to national data of 27 E.U. countries is presented, with a brief comment of the results.
Keywords: matematična statistika; statistične metode